2013
DOI: 10.1007/s40519-013-0084-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of meal consumption on emotion among individuals with eating disorders

Abstract: Findings indicate that individuals with BED have significantly different affective responses to eating non-binge meals than individuals with AN or BN. Data suggest changes in negative affect following meal consumption may be specific to certain ED diagnoses. Results provide preliminary evidence consistent with the idea that emotion states may function as maintenance mechanisms for psychopathology among ED diagnoses. Limitations and future directions pertaining to food-mood relationships for individuals with ED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Breakfast was provided in order to standardize the timing between meals. The breakfast calorie content (300 Calories) reflected a standard meal likely to be recommended during regular daily intake, and one that prior research has shown is consumable and less likely to induce severe anxiety in eating disorder participants in a research setting ( 38 , 39 ). The lunch calorie content (1,000 Calories) reflected an amount expected to be associated with aversive anticipation in individuals with AN, but not so high that it would be unreflective of a typical lunch meal consumed by an unaffected individual.…”
Section: Methodsmentioning
confidence: 99%
“…Breakfast was provided in order to standardize the timing between meals. The breakfast calorie content (300 Calories) reflected a standard meal likely to be recommended during regular daily intake, and one that prior research has shown is consumable and less likely to induce severe anxiety in eating disorder participants in a research setting ( 38 , 39 ). The lunch calorie content (1,000 Calories) reflected an amount expected to be associated with aversive anticipation in individuals with AN, but not so high that it would be unreflective of a typical lunch meal consumed by an unaffected individual.…”
Section: Methodsmentioning
confidence: 99%
“…Research using implicit and explicit measures has shown that typically rewarding experiences, such as viewing or consuming palatable foods [20,21,28,29] watching humorous videos [30,31], or perceiving prosocial emotions or touch [22,32,33] are less subjectively pleasant, and in some cases more aversive, for individuals with AN compared to HCs. Reward experiencing has been shown to engage similar brain structures as reward anticipation, most notably the ventral tegmental area and striatum interacting with the orbitofrontal cortex [15,17].…”
Section: Reward Experiencingmentioning
confidence: 99%
“…Prior characteristics of emotions spreaded in economic behaviour: gender differences of emotions experienced and social nature of that differences (Anderson et al, 2014;Cavanaugh et al, 2015;Godefroit-Winkel et al, 2019). But beyond that, certain phenomena are known as a result of consumption and emotion intersection and at the moment don't have a transfer to other areas.…”
Section: Problem Statementmentioning
confidence: 99%